Allergy to isothiazolinones in recent years - Ewa Nowakowska-Świrta; Marta Kieć-Świerczyńska (Nofer Institute of Occupational Medicine, 2020)
Background Isothiazolinones are preservatives which are present in cosmetics, household chemicals and many other industrial products. Initially, a mixture of methylchloroisothiazolinone and methylisothiazolinone (MCI/MI - Kathon CG) was used, and then, from the beginning of the 21st century, only methylisothiazolinone. Due to a significant increase in the number of contact dermatitis caused by allergy to this compound, it was withdrawn from leave-on cosmetics, and its concentration in rinse-off cosmetics was reduced. The aim of the study was to analyze the incidence of contact allergy to isothiazolinones among patients in the Nofer Institute of Occupational Medicine, Łódź, the intensification of patch test results and hypersensitivity depending on the occupation, and to assess the contribution of immediate allergy to the occurrence of that hypersensitivity. Material and Methods In a group of 1137 patients (832 females and 305 males) with suspected contact dermatitis, diagnosed in 2014-2018, patch tests series including methylchloroisothiazolinone/methylisothiazolinone (0.01%) and methylisothiazolinone (0.2%), produced by Chemotechnique Diagnostics, Sweden, were performed. In a group of 29 individuals with contact allergy to isothiazolinones, prick tests with methylisothiazolinone (0.001%, 0.01%, 0.1%, 1%) (Sigma-Aldrich, Germany) were conducted. Results Of the 1137 subjects, 95 (8.3%) were allergic to isothiazolinones, slightly more often females - 71 (8.5%) than males - 24 (7.9%). In total, 150 positive patch tests with isothiazolinones (13.2%) were obtained. The number of positive results with methylisothiazolinone alone (7.8%) was higher than the number with methylisothiazolinone from Kathon CG (5.4%). Among the subjects sensitized to methylisothiazolinone alone strongly positive patch tests (+++) concerned 60.7%. In the female group, office workers (42.3%) and medical staff (18.3%) predominated, and in the male group - locksmiths, turners, mechanics and similar ones (45.8%), and construction workers (25.0%). Prick tests with methylisothiazolinone were negative, and they became positive after 3-5 h. Conclusions Isothiazolinones, particularly methylisothiazolinone, are significant causal factors of contact allergy, including that of occupational origin. They have strongly allergenic properties, and in patch tests they often give very severe inflammatory reactions. The issue of the role of immediate allergy in the pathogenesis of isothiazolinones sensitization requires further research. Med Pr. 2020;71(5):603-11